High sensitivity troponin I in hypertrophic cardiomyopathy. (25th November 2020) - Osmanska, J; Connelly, A; Nordin, S; Vega, A; Simpson, J; Anusas, J; Findlay, I; Coats, C
Abstract: Background: ESC guidelines recommend measurement of troponin T in patients with hypertrophic cardiomyopathy (HCM) because high concentrations are associated with cardiovascular events, heart failure and death. The cardiac Troponin I subunit is not expressed in skeletal muscle making it a cardio-specific isoform. The use of troponin biomarkers in management of patients HCM is limited because concentrations only weakly correlate with clinical parameters. Most studies are small, and few have examined their relation with genotype and mortality. Purpose: To assess the relationship between high-sensitive troponin I (hsTnI) and characteristics of adults with HCM. Methods: Patients included were adults with an established diagnosis of HCM referred to a single centre for genetic testing. Demographic, clinical and imaging data were recorded at baseline. Echocardiography and cardiac magnetic resonance (CMR) were performed according to EACVI standards. Quantification of late gadolinium enhancement (LGE) was performed using the 5 SD quantitative threshold. Genotype was evaluated using a 16 gene panel in an accredited UK laboratory. Pathogenic and likely pathogenic variants were considered as a positive genotype. Serum hsTnI was measured by a two-site electrochemiluminescence immunoassay on a Roche E170 analyser. Normal values for the assay 0–34 ng/L for males and 0–16 ng/L for females. Results: 313 patients (n=200, 64% male) median age 57 (IQR 47–68) years were included. hsTnI concentration was abnormal in 69 (22%) patients. An abnormal hsTnI was more common in females (n=36, 32%) compared to males (n=33, 17%, c2 9.9, p<0.05). A pathogenic variant in a sarcomere gene was identified in 95 (30%) individuals. An abnormal hsTnI concentration was associated with higher left ventricular (LV) wall thickness (20mm v 18mm, p<0.05) and LV outflow tract (LVOT) gradient (34 v 22 mmHg) on echocardiography (n=313). Of the patients (n=204) who had a CMR, an abnormal hsTnI concentration was associated with higher LV mass (183 v 156g, p<0.05) and greater % LGE (30 v 16%, p<0.01, n=129). There was no difference in hsTnI between those with a positive or negative genotype. During follow-up, 18 patients died. Of the 9 patients that died with a normal hsTnI, two died suddenly. Conclusions: In HCM, patients with abnormal hsTnI concentration have higher LV mass and LVOT gradient and more fibrosis. Whilst mortality is higher in those with abnormal hsTnI, sudden cardiac death may occur with a normal hsTnI. It may not be appropriate to extrapolate hsTnI sex-specific thresholds used in the diagnosis of myocardial infarction to HCM. Funding Acknowledgement: Type of funding source: None